Do Land Markets Anticipate Regulatory Change? Evidence from Canadian Conservation Policy - Branko Boskovic; Linda Nøstbakken (Center for Economic Studies and ifo Institute (CESifo), 2016)
Regulation often evolves, and affected consumers or firms may adjust their behavior in anticipation of potential changes to regulation. Using shifting land use regulation boundaries and oil lease prices from Canada, we estimate the effect of anticipated regulatory change on the value of land. We find that anticipated rezoning decreases the price of unregulated leases. Based on our estimates, not accounting for anticipation underestimates the total cost of the regulation by nearly one-third. Overall, the evidence suggests that anticipation effects are significant and that the cost of anticipated regulation is capitalized into land values.
Keywords: Q58; D44; Q52; Q30; 330; regulation; anticipation; land values; zoning; oil leases; endangered species